Segmentation by Motivations in Sustainable Coastal and Marine Destinations: A Study in Jacó, Costa Rica - Carvache-Franco, Mauricio; Víquez-Paniagua, Ana Gabriela; Carvache-Franco, Wilmer; Pérez-Orozco, Allan; Carvache-Franco, Orly (Sustainability, 2022)
Coastal and marine tourism offers a wide variety of activities that can be sustainable due to the characteristics of its natural and cultural attractions. The present study was carried out in Jacó, a sustainable destination with coastal and marine characteristics of Costa Rica, with the objectives (i) of identifying the motivations of tourist demand; (ii) segmenting the tourist demand; (iii) establishing a relationship between the segments and sociodemographic aspects; and (iv) determining the relationship between segments of demand and satisfaction and loyalty. This quantitative study collected a sample of 304 valid questionnaires on-site in June 2021. For data analysis, a factorial analysis and non-hierarchical K-means segmentation were performed. The results show five motivational dimensions: “Learning and coastal experience”; “Nature”; “Rest and safety”; “Water sports”; and “Nightlife”—and three segments of tourists: “Multiple motives”; “Passive tourists”; and “Eco-Coastal”. The “Eco-Coastal” segment was the most satisfied in terms of enjoying the coastal nature of the destination. The “Multiple motives” group showed the highest intentions to return, recommend, and spread positive word of mouth. These findings will serve as management guides for coastal and marine destination managers and will help adapt these tourism sites to the new demand instigated by the global health crisis.
Artículo. Instituto Tecnológico de Costa Rica. Escuela de Administración de Empresas, 2022
Keywords: Segmentación; Turismo sostenible; Sostenibilidad; Aspectos sociodemográficos; Naturaleza -- Aprendizaje -- Seguridad; Deportes acuáticos; Vida nocturna; Sitios -- Turismo; Segmentation; Sustainable tourism; Sustainability; Sociodemographic aspects; Nature -- Learning -- Safety; Water sports; Nightlife; Sites -- Tourism; Research Subject Categories::SOCIAL SCIENCES::Business and economics